Low Vision Management in A 5-Years-Old Due to Retinopathy of Prematurity for Life Quality Improvement - Aritonang, Christina (Folia Medica Indonesiana, 2020)
Introduction: Management of low vision in pediatric patients with greater result can affect their quality of life than in adult low vision patients.. Retinopathy of Prematurity is the main cause of blindness in children. A case study highlights the tertiary prevention (low vision examination and management) in a 5 year old boy with ROP related blindness to optimize his remaining visual capacity by using optical and non optical aids that support daily activity and educational learning. Case Report: A 5 year old boy with ROP related blindness visited to the low vision clinic after receiving the several treatments for ROP before. His visual acuities were light perception in the right eye and hand movement in the left eye using his current spectacle correction. He had anti VEGF bevacizumab intravitreal injection, vitrectomy and complicated cataract extraction history on the left eye. He wasdifficult to learn and read numbers and alphabets caused by visual impairment. Discussion : Upon evaluation by assessment low vision method, his distance visual acuity in the left eye was improved significantly up to 3/40 on LEA Acuity chart with +14.00D. His near vision became 10 M at 30 cm of reading distance (without near correction) and 4 M at 13 cm improved with +3.00 D by spectacle. The non optical aid devices as reading task were also suggested to improove continuous reading text without difficulty. Conclusion: ROP blindness can be preventable if appropriate, adequate and accessible screening programmes are available. Unfortunately, even with the current screening guidelines and recommended treatment of ROP, many babies suffer from blindness by this disease each year. Low vision assessment and management in pediatric patient with visual impairmentaccording to children's need can optimize the recent visual capability of low vision patient and give self care daily activity and educational learning.